Negative Attitudes Towards Evaluation in Foreign Language Learning - Ghouar, Amor (Sciences humaines; Vol. 26 (2012): SCIENCES HUMAINES, 2014)
يهدف هذا المقال من خلال دراسة ميدانية بقسم اللغة الإنجليزية بجامعة باتنة  الى تسليط الضوء على نقطة تربوية هامة في تعليم اللغة الانجليزية في الطور الجامعي في النظام  الجديد(LMD) وهي نضرة الطلبة الى طريقة التقويم .إذ يعتبر الطلبة ان التقويم الذي يقتصر فقط على الأمتحان الكتابي لا يبين القدرات الحقيقية للطالب حيث ان اللغة الاجنبية لها جانب شفوي واخر كتابي بينما معضم طرق التقيم تخص الجانب الكتابي فقط.و من هنا فإن الطالب يتخذموقفا سلبيا من طريقة التقويم التي يعتبرها غير عادلة.واشار البحث على غقتراح بعض النقاط التي يمكن للأستاذ من خلالها تبسيط المفهوم العام للتقيم وجعته يتماشى مع القدرات الحقيقية للطالب.    It is generally agreed among teachers, learners and evaluators the terms assessment test and evaluation are used synonymously in most cases . In fact , when teachers quantify learner’s proficiency and mastery of language or one aspect of it, they are assigning him to a test through which they measure his abilities in order to evaluate him. As early as 1990,Bachman claimed that the similarities among these terms tend to obscure the distinctive characters of each. In foreign language education, the final objective is to enable communication in the target language. The need to measure students’ use of the learners language calls for an evaluation the type of evaluation use here is called evaluation of communicative competence.